OPPORTUNITIES OF VARIOUS IMMUNOLOGICAL TESTS IN DIAGNOSTICS OF TUBERCULOSIS IN HIV PATIENTS - A. A. Starshinova; A. M. Panteleev; V. V. Manina; E. V. Istomina; D. N. Afonin; V. Yu. Zhuravlev (Туберкулез и болезни лёгких)
Co-infection of tuberculosis and HIV-infection continues to be the current crucial issue not only due to the persistent growth of HIV-infection but also due difficulties in diagnostics of tuberculosis. Often X-ray changes in the lungs are atypical, clinical signs are manifested only in case of the severe and disseminated disease. At present the IGRA-tests are widely used worldwide while in Russia TRA tests are used. The trial provided the data on the use and comparative efficiency of the above immunological tests against Mantoux test with 2 TU when examining 239 persons from 2014 to 2015. The comparativeness of diagnostic sensitivity of all immunological tests had been proved. The specificity of IGRA-tests and TRA tests is twice higher compared to Mantoux test with 2 TU. Also it was proved that when diagnosing tuberculosis in HIV patients the skin tests (Mantoux test with 2 TU and TRA test) had low diagnostic informativeness compared to IGRA tests, among which ELISPOT was the most sensitive.